Combined intranasal and intramuscular parainfluenza 5-, simian adenovirus ChAdOx1- and poxvirus MVA-vectored vaccines induce synergistically HIV-1-specific T cells in the mucosa - Beavis, Ashley C.; Wee, Edmund G. -T.; Akis Yildirim, Belkis M.; Borthwick, Nicola; He, Biao; Hanke, Tomáš (Frontiers in Immunology, 2023)
Introduction The primary goal of this work is to broaden and enhance the options for induction of protective CD8+ T cells against HIV-1 and respiratory pathogens. Methods We explored the advantages of the parainfluenza virus 5 (PIV5) vector for delivery of pathogen-derived transgenes alone and in combination with the in-human potent regimen of simian adenovirus ChAdOx1 prime-poxvirus MVA boost delivering bi-valent mosaic of HIV-1 conserved regions designated HIVconsvX. Results We showed in BALB/c mice that the PIV5 vector expressing the HIVconsvX immunogens could be readily incorporated with the other two vaccine modalities into a single regimen and that for specific vector combinations, mucosal CD8+ T-cell induction was enhanced synergistically by a combination of the intranasal and intramuscular routes of administration. Discussion Encouraging safety and immunogenicity data from phase 1 human trials of ChAdOx1- and MVA-vectored vaccines for HIV-1, and PIV5-vectored vaccines for SARS-CoV-2 and respiratory syncytial virus pave the way for combining these vectors for HIV-1 and other indications in humans.